Effect of Different Saw Dust Substrates on the Nutritional Composition of Oyster Mushroom (Pleurotus florida) and its Applications in Human Health - Paul, Ratan Kumar; Bhattacharjya, Debu Kumar; Kabir, Abul Kalam Lutful; Rashid, Md Harun or; Rahaman, Md Samsur; Rahaman, Md Saifur; Miah, Md Nuruddin; Ahmed, Kamal Uddin (Dhaka University Journal of Pharmaceutical Sciences, 2016)
This study evaluated the effects of various sawdust substrates, namely Ficus carica (Fig tree, T2), Albizia saman (Rain Tree, T3), Swietenia mahagoni (Mahogany tree, T4), Leucaena leucocephala (Ipil ipil tree, T5), Eucalyptus oblique (Indian gum tree, T6) and mixture of mentioned five trees sawdust (T1) supplemented with 30% wheat bran and 1% lime on the mineral content and nutritional composition analyses of Plurotus florida mushroom. The highest amount of carbohydrate (43.68mg/100g), dry matter (9.87%), nitrogen (4.43%), potassium (1.39%), magnesium (19.96mg/100g) and iron (44.69mg/100g) were obtained from T4 sawdust substrate. The highest amount of phosphorous (0.89%) was obtained from T1 substrate. The highest amount of lipid (4.21%), protein (27.68%), ash (13.67%), moisture (90.27%) and molybdenum (9.76mg/100g) were obtained from T2 sawdust substrate. The lowest amount of lipid (3.42%) was found for T6 substrate. The highest amount of crude fiber (19.78%), calcium (33.35mg/100g) and selenium (9.10 mg/100g) were obtained from T5 substrate. The highest amount of cobalt (21.07mg/100g) and zinc (30.26mg/100g) were obtained from T3 sawdust substrate. Thus, they could be an excellent source of many different nutraceuticals and might be used directly in human diet to promote health for the synergistic effects of all the bioactive compounds present. The study proved beneficial for effective management of agricultural wastes as well as production of nutraceutical effective fruiting bodies for balanced diet. Dhaka Univ. J. Pharm. Sci. 14(2): 215-223, 2015 (December)